Effect of viscous soluble dietary fiber on glucose and lipid metabolism in patients with type 2 diabetes mellitus: a systematic review and meta-analysis on randomized clinical trials - Lu, Kun; Yu, Tingqing; Cao, Xinyi; Xia, Hui; Wang, Shaokang; Sun, Guiju; Chen, Liang; Liao, Wang (Frontiers in Nutrition, 2023)
Background The effect of viscous soluble dietary fiber on glucose and lipid metabolism in type 2 diabetes mellitus (T2DM) remains controversial, and the dose–response relationship of its effect on blood glucose and blood lipid level is still unclear. Methods We conducted comprehensive searches in several databases up to 17 January 2023. We conducted a dose–response analysis of randomized controlled trials (RCTs) to investigate the effect of viscous dietary fiber on glucose and lipid metabolism in patients with T2DM. Results Statistical significance was observed in the decreases of glycosylated hemoglobin (HbA1c) (mean difference) [MD = −0.47; 95%CI: (−0.66, −0.27)], fasting blood glucose (FBG) [MD = −0.93; 95%CI: (−1.46, −0.41)], total cholesterol (TC) [MD = −0.33; 95%CI: (−0.46, −0.21)], and low-density lipoprotein and cholesterol (LDL-C) [MD = −0.24; 95%CI: (−0.35, −0.13)]. Contrarily, no difference was observed regarding the level of high-density lipoprotein cholesterol (HDL-C) or triglyceride (TG). In addition, the effect on fasting insulin remains unclear. Results from the subgroup analyses showed that an intervention duration longer than 6 weeks had a significant effect on the HbA1c level; a treatment dosage higher than 8.3 g/day had a significant effect on the FBG level. Conclusions Supplementation of viscous dietary fiber is beneficial to control blood glucose and blood lipid in T2DM.